7(x-4)=6(x+1)-3

Simple and best practice solution for 7(x-4)=6(x+1)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-4)=6(x+1)-3 equation:


7 (x-4)=6(x+1)-3

We simplify the equation to the form, which is simple to understand
7(x-4)=6(x+1)-3

Reorder the terms in parentheses
+(+7x-28)=6*(x+1)-3

Remove unnecessary parentheses
+7x-28=+6+*(+x+1+)-3

Reorder the terms in parentheses
+7x-28=+(+6x+6)-3

Remove unnecessary parentheses
+7x-28=+6x+6-3

We move all terms containing x to the left and all other terms to the right.
+7x-6x=+6-3+28

We simplify left and right side of the equation.
+1x=+31

We divide both sides of the equation by 1 to get x.
x=31

See similar equations:

| 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) | | 8n-3.5=-20 | | z/2+1=7z/2 | | 10(1+30b)=-20 | | 2x+8-k=-3 | | 24-4= | | 20z+80=140+10x | | -(3x-2)-(x+4)=-(2x-2)-(2x+4) | | 10+30b=-2 | | 11520=32x^2+64x | | 9x-4x-15=-35 | | 2(6x)+2(8x-10)= |

Equations solver categories